(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Oral squamous cell carcinoma (OSCC) is a major public health problem in India, largely due to tobacco, areca nut, and alcohol use. Oral potentially malignant disorders (OPMDs) can progress to OSCC, but predicting this transformation is difficult. Therefore, reliable biomarkers such as p63, which regulates epithelial proliferation and differentiation, are needed to improve diagnosis and risk assessment. Aim & Objectives: To evaluate the expression of p63 in normal oral mucosa, OPMDs, and OSCC, and to determine its diagnostic and prognostic significance by correlating its expression with histopathological grading and disease progression. Materials & Methods: This immunohistochemical study analyzed tissue samples from normal oral mucosa, OPMDs with varying grades of epithelial dysplasia, and OSCC. p63 expression was assessed based on nuclear staining pattern, labeling index, and distribution within epithelial layers. The findings were correlated with histopathological grades and relevant clinical parameters to evaluate the role of p63 in oral carcinogenesis. Results: In normal oral mucosa, p63 expression was restricted to the basal and parabasal cell layers. OPMDs exhibited increased p63 expression with extension into suprabasal layers, which correlated with the severity of epithelial dysplasia. The highest expression was observed in OSCC, showing diffuse and intense nuclear staining. A progressive increase in labeling index was noted from normal mucosa to dysplasia and carcinoma. Furthermore, elevated p63 expression was associated with poorer tumor differentiation and more aggressive biological behavior. Conclusion: p63 is a valuable immunohistochemical biomarker for evaluating epithelial dysregulation and malignant transformation in oral lesions. Its progressive overexpression from normal mucosa to OSCC supports its utility in early diagnosis, risk assessment, and prognostic evaluation, although it should be used as an adjunct to conventional histopathology.